A novel GABA receptor on bipolar cell terminals in the tiger salamander retina - Lukasiewicz, PD (J Neurosci, 1994)
We studied the pharmacology of the GABA receptors on bipolar cell terminals in the retinal slice preparation. Whole-cell patch-clamp recordings were made from the somas of bipolar cells and GABA was puffed near their terminals, after synaptic transmission was blocked. GABA puffs evoked a large chloride current that was reduced by picrotoxin, but in many cells this current was insensitive to blockade by the competitive GABAA receptor antagonists bicuculline and SR95531. Pentobarbital, an enhancer of GABAA receptor-mediated responses, did not significantly increase the magnitude of the current responses to GABA puffed at the bipolar cell terminals. To confirm the effectiveness of GABAA antagonists and pentobarbital in the slice preparation, we measured GABA currents in ganglion cells. In contrast to bipolar cells, the ganglion cell GABA responses were strongly reduced by both bicuculline and SR95531. In addition, pentobarbital strongly enhanced the action of GABA at the ganglion cells. The isomeric GABA agonists cis- and transaminocrotonic acid (CACA and TACA), elicited picrotoxin- sensitive currents in both bipolar and ganglion cells. TACA was more effective than CACA at both cell types. In bipolar cells, TACA and CACA currents were relatively resistant to bicuculline blockade, but in ganglion cells both currents were reduced by bicuculline. GABA receptors on bipolar terminals appear to be pharmacologically different from the GABA receptors found on ganglion cell dendrites. The bipolar cell terminal GABA receptor pharmacology is similar to the pharmacology reported for the rho 1 GABA receptor subunit that was isolated from retina and expressed in Xenopus oocytes (Cutting et al., 1991; Polenzani et al., 1991; Shimada et al., 1992). This receptor, which is both bicuculline and pentobarbital insensitive, has been called the GABAC receptor (Johnston, 1986; Shimada et al., 1992). However, some bipolar cells were somewhat sensitive to blockade by bicuculline, suggesting that these cells had both GABAA and GABAC receptors on their bipolar terminals.